'The Same Trade as Mozart': Convincing the sceptics of electronic music's value. Issue 1 (1st March 2021) - Morgan, Frances; Mooney, James
In August 1969, the music documentary series Workshop (1964‐78) focused on electronic music in a 55-minute-long film titled 'The Same Trade as Mozart'. Produced and directed by David Buckton, the film included interviews with composers Karlheinz Stockhausen, Tristram Cary and Justin Connolly; BBC Radiophonic Workshop staff Desmond Briscoe, David Cain and John Baker, and the Workshop's founder, Daphne Oram; and Peter Zinovieff, director of EMS (Electronic Music Studios). It presented electronic music in a number of contexts, such as education, pop production and live performance. Technological change in music has often provoked hostility among the public and critics, and the rapid advancement of electronic music post-Second World War was no exception. Adopting a mode of analysis more commonly encountered in studies of the public communication of science, this article considers 'The Same Trade as Mozart' as an attempt by electronic music's advocates, such as those listed above, to convince sceptics of its value. While sceptical responses to the presence of new technologies in music have been widely noted and theorized by scholars in science and technology studies, we call attention to the strategies employed by the advocates of such technologies to defend themselves against such criticisms, including humour, heuristic explanations and a focus on electronic music's educational and thus social value. The use of computers in electronic music was a new and contentious development in the field, requiring a greater degree of advocacy from its proponents. We examine how the computer's role in composition is presented in 'The Same Trade as Mozart', compared with other media portrayals of computing in the 1960s. Drawing on theories of filmed musical performance, we discuss how visual tropes of 'classical' music are used in 'The Same Trade as Mozart' to challenge preconceptions about the relationships between composers, musicians and new technologies.